Adipositas cordis: a challenging differential diagnosis - Cristiane Rúbia Ferreira; Fernando Peixoto Ferraz de Campos; Jorge Isaac Garcia Paez (University of São Paulo, 2011)
Myocardial fatty infiltration is a diagnostic challenge for clinicians and pathologists once it may be found as part of normal myocardial tissue or may be a manifestation of diseases responsible for fatal outcomes like sudden death, arrhythmias and heart failure. Differential diagnosis between the diseases related to myocardial fatty infiltration as, Adipositas Cordis and Arrhythmogenic Dysplasia of the Right Ventricle requires clinical, laboratory and histopathological correlation. The authors present a case of a previously healthy patient, non obese, who unexpectedly presented a refractory hypotension after a physiologic stress characterized by immediate post operatory. The necropsy findings showed fatty infiltration of the heart characterizing the histological features of Adipostas Cordis. This finding explained the right ventricle failure and consequent refractory hypotension.